2013
DOI: 10.1111/jpn.12120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pistachio by‐products in replacement of alfalfa hay on populations of rumen bacteria involved in biohydrogenation and fermentative parameters in the rumen of sheep

Abstract: The objective of this study was to investigate the effect of sundried pistachio by-products (PBP) as a replacement of alfalfa hay (AH) on blood metabolites, rumen fermentation and populations of rumen bacteria involved in biohydrogenation (BH) in Baluchi sheep. Four adult male Baluchi sheep (41 ± 1.3 kg, BW) fitted with ruminal cannulae were randomly assigned to four experimental diets in a 4 × 4 Latin square design. The dietary treatments were as follows: (i) control, (ii) 12% PBP (0.33 of AH in basal diet re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 42 publications
5
21
1
1
Order By: Relevance
“…In particular, a negative relationship has been observed between the amount of total phenols contained in BPRP (expressed in g/kg DM) and DMI (expressed in kg/d) only in sheep (y = 22.872x + 47.765; R 2 = 0.8118) [16,[88][89][90][91], as reported in Figure 2. In contrast, in goats, this association was not observed (y = −1.2727x + 18.586 R 2 = 0.0003; Figure 2) [40,[92][93][94]. Probably, considering their different feeding behaviors (goats are intermediate feeders and ewes are grazers) [95], goats developed more strategies against these types of feeds rich in polyphenols (e.g., the presence of proline-rich proteins in the saliva [96] and a higher capacity of the saliva to bind tannins [97][98][99][100], which can help this species better control the toxicity of tannins than grazers [101].…”
Section: Effect On Voluntary Feed Intakementioning
confidence: 90%
“…In particular, a negative relationship has been observed between the amount of total phenols contained in BPRP (expressed in g/kg DM) and DMI (expressed in kg/d) only in sheep (y = 22.872x + 47.765; R 2 = 0.8118) [16,[88][89][90][91], as reported in Figure 2. In contrast, in goats, this association was not observed (y = −1.2727x + 18.586 R 2 = 0.0003; Figure 2) [40,[92][93][94]. Probably, considering their different feeding behaviors (goats are intermediate feeders and ewes are grazers) [95], goats developed more strategies against these types of feeds rich in polyphenols (e.g., the presence of proline-rich proteins in the saliva [96] and a higher capacity of the saliva to bind tannins [97][98][99][100], which can help this species better control the toxicity of tannins than grazers [101].…”
Section: Effect On Voluntary Feed Intakementioning
confidence: 90%
“…Recent molecularly based microbial identifications have advanced our understanding of the composition and function of rumen microbiota. Many efforts have been made to survey rumen microbiota, revealing that numerous factors can affect the rumen microbial composition, with diet being the main driving force for the microbial compositional shift (9). In addition, multiple studies have reported the "core rumen microbiota" in beef cattle (6,10) and dairy cows (11,12), as well as that among all ruminants (13).…”
mentioning
confidence: 99%
“…Use of dry PH up to 36% in sheep ration did not affect the relative abundance of rumen bacteria involved in biohydrogenation (Ghaffari et al, 2014a). Further, Sedighi-Vesagh et al, (2015) indicated that to an increase in polyunsaturated fatty acids content in milk fat of goats as a result of inclusion of dry PBM at level of 32% of total dietary DM and he related that to a modifications in biohydrogenation of fatty acids in the rumen.…”
Section: Lipids Metabolismmentioning
confidence: 95%
“…It has been reported that the use of dry PH 36% -50% (Ghasemi et al, 2012b;Ghaffari et al, 2014a) in sheep rations decreased the concentration of volatile fatty acids in the rumen. Dry PBM replaced alfalfa hay (30% of the dietary DM) in the diet of dairy goats without any effects on the profile of volatile fatty acids (Ghaffari et al, 2014b).…”
Section: Carbohydrate Metabolismmentioning
confidence: 97%
See 1 more Smart Citation